Compact wideband four-element MIMO antenna with high isolation - Saurabh A.K.; Rathore P.S.; Meshram M.K. (My University, 2025)
A compact wideband four-element multiple-input-multiple-output (MIMO) antenna with high isolation is proposed in this Letter. The proposed MIMO antenna consists of a tapered microstrip line fed rectangular monopole antenna arranged in orthogonal symmetric fashion on the interconnected partial ground plane. The overall size of the proposed antenna is 35 × 35 × 0.8 mm3 with 9.5 mm edge-to-edge separation between a pair of radiating elements. The proposed MIMO antenna has a -10 dB fractional impedance bandwidth of 49.57% covering 4.4-7.3 GHz, encompassing sub-6 GHz 5G (4.5 GHz), WLAN (5/5.2/5.8 GHz), WiMAX (5.5 GHz), HYPERLAN/1, 2, and ISM bands (5.2/5.8 GHz) applications. The proposed MIMO antenna has a minimum isolation value of 21 dB, maximum envelope correlation coefficient (ECC) value of 0.014 between antenna elements throughout the band. The measured results are found in good agreement with the simulated S-parameters, radiation patterns, ECC, total active reflection coefficient, and channel capacity loss. © The Institution of Engineering and Technology 2020.